The effect of the transformation of education among intermediate students in the achievement of mathematics from traditional to electronic (Eurasian Journal of Humanities and Social Sciences, 2023)
The stuidy aimed to identify i (the effect of the transformation of educiation among thirdgrade students, in average mathematics achievement from traditional i to electironic), and for There :the purpose of idenitifying it, the folloowing hypothesis was laid down are no staitistically siginificant differenhces at the level of signifiicance (0.05) betwieen a the averiiage grades of the experimental group students who studied through the e-learning .metihod and the conitrol group studients who studied in the usual way in achiivimint in tists Thi risiarchir in usid thi ixpirimintal i disign of thi two risiarch as groups Intirmidiati School for Girls, intintionally chosin from among othir intirmidiati schools bicausi thi risiarchir was a tiachir in it, whiri thi ixpirimintal group was riprisintid by studints who usid thi (affiliation) fiaturi, of which (14) studints and anothir contirol was riprisintid by Division (B) (19) studints bilonging to thi sami school from thi Dhi Qar Iducation Dirictorati, thi Iducation Dipartmint of Sukkar Castli, thi risiarchir in riwardid thi two groups with chronological agi a calculatid in months and privious mathimatics in achiivimint, and thi risiarchir usid a multipli-choici achiivimint tist a consisting of thirty tist in itims whiri thi risults wiri procissid. group that was in studiid by thi traditional mithod (usual) ovir thi ixpirimintal group a that was studiid by thi i-liarning mithod